Inventarisasi Keanekaragaman Lumut Di Kawasan Kampus 1 UIN Sunan Gunung Djati Bandung - Aulia Rahmi, Hilyah; Wulan Cahyani, Hilda; Supriatna, Ateng (Jurnal Ilmu Pertanian dan Perkebunan, 2023)
The diversity of vegetation on the UIN Sunan Gunung Djati Bandung Campus has good potential because even though the campus is in the middle of an urban area with moderate rainfall intensity it can have an impact on moss growth. Moss has a very important role within the scope of the ecosystem because it is useful for reducing the danger of flooding, helping to maintain humidity, as a producer of O2 because it can carry out photosynthesis in a short time and has a function as an absorbent of pollutants so that it can be used as a bioindicator of polluted air, besides that can be used as medicine. Observations of moss plants were carried out in the campus area 1 of UIN Sunan Gunung Djati Bandung by tracing to several location points and documenting the mosses found and identification using related literature studies by looking at their morphology. The observation results obtained 6 species of moss namely Calymperes erosum, Dumortiera hirsuta, Funaria hygrometrica, Tortula muralis, Leucoloma molle, and Candelariella spraguei. One of the roles of mosses in ecosystems is as an inhibitor of erosion, mosses can be used as medicinal ingredients, as well as organisms capable of decontaminating water and soil.